Ligand autoradiographical quantification of histamine H(3) receptor in human dementia with Lewy bodies - Lethbridge, Natasha L. (Pharmacol Res, 2016)
Dementia with Lewy bodies (DLB) is a serious age-dependent human neurodegenerative disease, with multiple debilitating symptoms, including dementia, psychosis and significant motor deficits, but with little or no effective treatments. This comparative ligand autoradiographical study has quantified histamine H(3) receptors (H(3)R) in a series of major cortical and basal ganglia structures in human DLB and Alzheimer’s (AD) post-mortem cases using the highly selective radioligand, [(3)H] GSK189254. In the main, the levels of H(3) receptor were largely preserved in DLB cases when compared with aged-matched controls. However, we provide new evidence showing variable levels in the globus pallidus, and, moreover, raised levels of Pallidum H(3) correlated with positive psychotic symptoms, in particular delusions and visual hallucinations, but not symptoms associated with depression. Furthermore, no correlation was detected for H(3) receptor levels to MMSE or IUPRS symptom severity. This study suggests that H(3)R antagonists have scope for treating the psychotic symptomologies in DLB and other human brain disorders.